A Message From The Chalk Face – What Casual Teaching Staff Tell Us They Want To Know, Access and Experience. - Brown, Natalie; Kelder, Jo-Anne; Freeman, Brigid; Carr, Andrea (Journal of University Teaching and Learning Practice, 2013)
The University of Tasmania established a project in 2009 to investigate the particular needs of casual teaching staff, identify strategies to improve access to information, and facilitate a consistent approach to employment, induction, development and recognition. The project was managed by the university learning and teaching centre, and co-ordinated by a Reference Group. A preliminary survey in 2010 explored casual teaching staff information and resource needs and a mapping exercise was undertaken to establish institutional practices. The findings of the preliminary 2010 survey and mapping exercise prompted the development of an institution-wide Casual Teaching Staff Policy. The preliminary 2010 survey was subsequently updated and a second survey administered in 2012 to obtain additional baseline data against which to evaluate the casual teaching staff project and implementation of the Casual Teaching Staff Policy. This paper presents the results of the 2012 survey designed with this dual focus in mind. The 2012 survey items were explicitly aligned to the Sessional Staff Standards Framework arising from the Benchmarking Leadership and Advancement of Standards for Sessional Teaching (BLASST) project. The 2012 survey results were mapped to the Sessional Staff Standards Framework guiding principles (Quality Learning and Teaching, Sessional Staff Support and Sustainability), standards (Good Practice, Minimum Standard, Unsustainable), and criteria spanning different institutional levels (Institutional Level, Faculty Level, Department Level, Individual Level). Together the quantitative and qualitative survey data results provide a rich depiction of the world of casual teaching staff at the University of Tasmania. On the one hand the results evidence examples of well-supported, fully engaged casual teaching staff; on the other hand, a distressing picture emerges for many such staff. The findings are presented with discussion regarding the requisite ensuing steps in this ongoing initiative to improve the employment, induction, development and recognition experiences of University of Tasmania casual teaching staff.